Stop Bullying Sejak Dini: Strategi Mahasiswa KKN Dalam Mengedukasi Siswa SD di Desa Guntung - Heriyani Heriyani; Maysarah; Jihan Irtama; Marsyah Finkan Aditya; Nurul Anissa; Samio (LPPI UMN AL WASHLIYAH, 2025)
Bullying is a serious problem that frequently occurs in elementary schools and negatively impacts students' psychological development and academic achievement. Instilling anti-bullying attitudes from an early age is a crucial step in creating a safe, comfortable, and child-friendly school environment. This article discusses the strategies implemented by Community Service Program (KKN) students in educating elementary school students about bullying prevention and management. The methods used included interactive outreach and the screening of motivational videos. The results of the activities showed an increase in students' understanding of the types of bullying, their impacts, and how to report and prevent bullying. This KKN program is expected to become an effective model for sustainable education in building a culture of mutual respect and fostering positive character in elementary school students.